Deflecting responsibility: spirits in Southeast Asia and "systems" in Western modernity - Sprenger, Guido (Hau, 2022)
While studies of responsibility have been concerned with the ways responsibility is traced to accountable human persons or institutions, the deflection of responsibility to nonhumans that are not accountable has been neglected. Such deflections may follow at least two different procedures. The Rmeet in Laos sometimes opt to deflect responsibility for wrongdoing to spirits who temporarily obfuscate a person’s intentionality. People in modern contexts, in contrast, occasionally delegate responsibility to impersonal sets of rules and laws—the “system,” the “market,” “nature.” In both cases, concepts of personhood condition the shape of the nonhumans emerging from the distribution of agency. Persons appear as forms that differentiate between actions that can be integrated into them and those that cannot. The deflection of responsibility protects personal integrity from actions incoherent with a person’s form. In particular, deflection to nonhumans removes accountability from the sphere of human influence.